Evaluating the implementation of web-based Merdeka Curriculum e-report cards in elementary schools in Salatiga using the CIPP model - Maria Cristiana Yuliyanti Djari; Sophia Tri Satyawati; Wasitohadi (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2025)
E-report cards in the Merdeka curriculum are a significant educational innovation. Evaluation of using e-report cards that focuses on the technical and practical aspects of implementing web-based e-report cards in elementary schools is rare, especially in Salatiga. The problems have not been identified, such as application bugs, synchronisation problems with Dapodik, or high hardware requirements. This study uses the Context, Input, Process, Product (CIPP) evaluation model developed by Daniel Stufflebeam. The context shows that implementing e-report cards cannot be carried out due to inadequate infrastructure. The evaluation input shows that technical training for teachers has not been obtained evenly, with only one teacher and OPS in 2022. The process does not exist because inputting values ​​​​or synchronisation has not been implemented. Product evaluation of the e-report card results and qualities cannot be assessed. The school decided to postpone the implementation of this system until the infrastructure, training, and official policies are available. Google Spreadsheets are currently used to process grades in schools. This system is considered more effective and easier to use by all teachers (user-friendly), reports quickly and can be accessed in real-time without needing to be on the same server as long as the internet remains.